Оптимизация элементов конструкций по прочностным и динамическим характеристикам - Симсон, Эдуард Альфредович; Назаренко, Сергей Александрович; Анацкий, Юрий Петрович (НТУ "ХПИ", 2004)
Structural optimization methods of high both geometric and physical informational content are suggested for complicated FEA models, especially with design variables vector of high dimension, to minimize numbers of straight calculation procedure activation. Computational stages are investigated. The developed mathematical apparatus application are examined.
Keywords: машиностроительные конструкции; системы проектирования; методы оптимизации; область варьирования; метод конечных элементов; метод последовательной линеаризации